Solid State Characterization of Acyclovir-Nicotinamide Binary Systemsusing Solvent Evaporation Technique - Winantari, Agnes Nuniek (2016)
Objective of the study is to characterize acyclovir-nicotinamide binary systems (AN). Methods ofcocrystallization wassolvent evaporation in equimolar ratio between acyclovir and nicotinamide using ethanoland methanol. The binary systems were characterized by polarization microscope, Differential ScanningCalorimetry (DSC) and Powder X-Ray Diffraction (PXRD). Physical characterization showed that AN binarysystems have unique crystal habit in microscopic. A new endothermic peak appears at 123.69 C. The PXRDpatterns of AN binary systems after cocrystallization are different from pure components which specific peakwasfound on 2θ = 11.27 o (AN in ethanol); 21.05 o (AN in methanol).